Pembelajaran Al-Qurâ€™an di Pesantren Tahfidz Khusus Anak Al-Azka, Cisauk Tangerang, Banten - Huliyah, Muhiyatul (ACIECE, 2017)
The study was conducted in Al-Azka tahfidz pesantren special for children, Cisauk Tangerang,Banten. Tahfidz pesantren which started at 2012-2013 is an Islamic boarding school institutionspecial for children aged 5-12 years and has three education system. Those are: (1) tahfidzeducation system, that is integrating Yanbu'ul Qur'an Kudus Central Java tahfidz educationsystem with the national education system of elementary school that has been innovated (2)language education system applied using Arabic system of Gontor Pesantren curriculum thatsantri able to communicate fluently and well. (4) SDTQ Al-Azka (Al-Azka Tahfidzul Qur'anElementary School) which study every day and used GBPP (outline for teaching program)system. The curriculum applied by the ministry of national education (diknas). Al-Azka tahfidzpesantren special for children is an educational institution with the main program is tomemorize the Qur'an with the target of elementary school graduation memorized 30 juz. Thelearning process of the Qur'an are: tashih makhroj, tashih huruf (letters), tajwid, and tahfidz, withtargets as follows: Class I: the targets set are they have the ability to read smoothly, finished bi alnazor reading and memorize juz 30 (juz 'amma). Class II: the target set is the santri (learner) ableto memorize 5 juz (juz 1-5). Class III: the target set is the santri able to memorize 6 juz (juz 6-11).Class IV: target set is santri able to memorize 6 juz (juz 12-17). Class V: target set is the santrimemorize 6 juz (juz 18-23). Class VI: the target set is the santri able to memorize 6 juz (juz 24-30). The â€œquarantine programâ€ is done for the santri (Class VI) who are not yet memorized 30juz. This program hopes that the santri who passed elementary school have the ability tomemorize 30 Juz.